2020
DOI: 10.2166/wcc.2020.207
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological drought risk recurrence under climate change in the karst area of Northwestern Algeria

Abstract: This study aims to estimate hydrological drought risk using probabilistic analysis of bivariate drought characteristics to assess both past and future drought severity and duration in three basins located in the widest karst massif of northern Algeria. The procedures entail: (1) identification of extent of meteorological drought that could trigger corresponding hydrological drought through their characteristics; (2) assessment of future risk of extreme drought according to two emission scenarios of the represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 124 publications
1
21
0
Order By: Relevance
“…The climate in Northwestern Algeria was humid in 1951, semi-arid since 1973 and it is projected to be arid in 2100. Bouabdelli et al (2020) also found that hydrological drought risk determined with S. Bouabdelli et al: Past and future drought in Northwestern Algeria: the Beni Bahdel Dam catchment frequency analysis likely will rise especially under RCP8.5 with higher severities and durations.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The climate in Northwestern Algeria was humid in 1951, semi-arid since 1973 and it is projected to be arid in 2100. Bouabdelli et al (2020) also found that hydrological drought risk determined with S. Bouabdelli et al: Past and future drought in Northwestern Algeria: the Beni Bahdel Dam catchment frequency analysis likely will rise especially under RCP8.5 with higher severities and durations.…”
Section: Introductionmentioning
confidence: 87%
“…Several studies also published drying trends in the Western Mediterranean region starting at different times, i.e. from the mid-1920's to 1950 and since the mid-1970's (Brunet et al, 2007;Zeroual et al, 2019). The vast plains of the western region of Algeria are an important agricultural production and farming zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, climate change has meant that recurrent, severe, and widespread droughts will become a common phenomenon in the future [1,2], with adverse implications on water supply [3]. In drought-prone areas, persistent droughts can intersect with other drivers of water scarcity, such as population growth, unsustainable consumption and poor management of water, and legacies of inequality and uneven social vulnerabilities, which collectively result in adverse impacts on different sectors including agriculture, energy, and health [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding climate variability, climate change and global warming is essential for understanding world's water cycle. Understanding the various components water cycle's components has been the aim of a large body of studies on rainfall, flow, temperature, evaporation, infiltration (Mengistu et al, 2021;Dang et al, 2021;Pokharel et al, 2020;Nistor et al, 2020;Li et al, 2020;Bouabdelli et al, 2020;Zerouali et al, 2020;Machiwal et al, 2019;Pathak et al, 2017;Santos et al, 2018;Gocic and Trajkovic 2014;Duncan et al, 2013;Meddi et al, 2010) to be the key elements in designing and managing civil engineering structures, particularly studies on the precipitation component (Wolski et al, 2021;Martinez-Artigas et al, 2020;Zerouali et al, 2021;Machiwal et al, 2019;Lazri and Ameur, 2018;Teodoro et al, 2015;Conway et al, 2010;Massei et al, 2011). Studies on rainfall are the most common compared to the other components; thus, the results of these works can help managers in decision-making processes in the field of water resources.…”
Section: Introductionmentioning
confidence: 99%